2017
DOI: 10.1097/scs.0000000000003558
|View full text |Cite
|
Sign up to set email alerts
|

Periorbital Soft Tissue Anthropometric Analysis of Young Adults

Abstract: The authors aim to determine the periorbital soft tissue anthropometric norms for Turkish young adults for right and left eyes using a noninvasive two-dimensional photogrammetric analysis. Anthropometric measurements of the periorbital soft tissue were taken from 172 female and 56 male Turkish adults aged between 18 and 24 years. The periorbital soft tissue profiles (ocular and palpebral) for males and females were digitally analyzed using linear measurements made with standardized photographic records, taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Aksu et al 51 found this distance as 48.31 AE 4.44 mm in males and 51.35 AE 3.38 mm in females shorter than other studies. In addition to Ozdemir et al, 1 Gudek and Uzun 50 and Vasanthakumar et al 43 stated that, as in this study, males were found to have statistically higher values than females. However, unlike other studies, Aksu et al 51 reported that this distance is statistically higher in females.…”
Section: Discussionsupporting
confidence: 62%
“…Aksu et al 51 found this distance as 48.31 AE 4.44 mm in males and 51.35 AE 3.38 mm in females shorter than other studies. In addition to Ozdemir et al, 1 Gudek and Uzun 50 and Vasanthakumar et al 43 stated that, as in this study, males were found to have statistically higher values than females. However, unlike other studies, Aksu et al 51 reported that this distance is statistically higher in females.…”
Section: Discussionsupporting
confidence: 62%
“…1). These cohorts included African (n = 15), 1,16–26 Asian (n = 22), 1,6,19,24,27–41 White (n = 37), 1,16,24,33,34,38,42–52 Hispanic (n = 6), 53–55 Middle Eastern (n = 21), 1,9,10,42,56–67 and Southeast Asian (n = 17) 1,33,37,68–77‚78 participants. The majority (n = 52/67, 77.6%) of studies strictly included participants between the ages of 16 and 40, with a homogeneous distribution between men (49.8%) and women (50.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are many studies in the literature on anthropometric measurements related to the face in Turkey, there are a limited number of anthropometric studies on the periocular region in the Turkish population in the current literature. [23][24][25] This study provides detailed information for both genders in the 10 to 25 years age range in Turkey and demonstrates the developmental changes that occur in the periocular region.…”
Section: Discussionmentioning
confidence: 99%